A triazine-based covalent organic framework/palladium hybrid for one-pot silicon-based cross-coupling of silanes and aryl iodides. Issue 51 (6th May 2015) - Lin, Sha; Hou, Yuxia; Deng, Xiao; Wang, Haoliang; Sun, Shuzhuang; Zhang, Xiaomei
Abstract : A palladium/COF hybrid material could efficiently catalyze the silicon-based one-pot cross-coupling reaction of silanes and aryl iodides with excellent selectivity. Abstract : A triazine-based covalent organic framework (COF-SDU1 ) was synthesized through facile solvothermal conditions and characterized by IR, solid state 13 C NMR, XRD, elemental analysis and BET. By a simple solution infiltration method, Pd(ii ) species were successfully immobilized intoCOF-SDU1 due to its two-dimensional eclipsed layer-sheet structure and nitrogen-rich content. High-resolution TEM images showed the uniform loading of the Pd species into theCOF-SDU1 matrix. By using this hybrid material, Pd(ii )/COF-SDU1, as a sustainable and green catalyst, one-pot cross-coupling of silanes and aryl iodides was realized with high selectivity. The catalyst can be easily recovered by a simple separation process and recycled several times without obvious loss of activity and selectivity.